YAŞLILIKTA KARACİĞER HASTALIKLARI - ÖZDEMİR, Sebati (Cerrahpaşa Medical Journal, 2014)
Background.- Although there is no liver disease being unique to advanced age, there are important differences in the clinical presentation, course and prognosis of liver diseases in older patients compared with younger patients. In this article, the alterations in the liver and the clinical features of liver diseases seen in the elderly were reviewed.